2019
DOI: 10.1016/j.lindif.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Beyond academic achievement goals: The importance of social achievement goals in explaining gender differences in self-handicapping

Abstract: Boys show less adaptive behaviour and engagement than girls at school. Much research has examined gender differences in academic motivation to explain gender differences in school engagement. However, students engage in schools both academically and socially, and gender differences in social motivation may further contribute to the gender gap in academic engagement. In this study, 536 secondary school students in England (ages 13-14) reported their social achievement goals, academic achievement goals, and self… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Meanwhile, academic effort is perceived as uncool during adolescence, and adolescent boys and girls displaying high effort are rated by their peers as lower in popularity (Heyder and Kessels 2017). Given this conflict between school effort and peer status, young people with the desire to gain or maintain peer approval tend to purposely withhold effort in school (Yu and McLellan 2019). Indeed, cool guys, modern girls, and wild girls in the current study reported low perseverance and frequent use of effort withdrawal as a self-handicapping strategy.…”
Section: Which Boys and Which Girls Are Falling Behind In School?mentioning
confidence: 99%
“…Meanwhile, academic effort is perceived as uncool during adolescence, and adolescent boys and girls displaying high effort are rated by their peers as lower in popularity (Heyder and Kessels 2017). Given this conflict between school effort and peer status, young people with the desire to gain or maintain peer approval tend to purposely withhold effort in school (Yu and McLellan 2019). Indeed, cool guys, modern girls, and wild girls in the current study reported low perseverance and frequent use of effort withdrawal as a self-handicapping strategy.…”
Section: Which Boys and Which Girls Are Falling Behind In School?mentioning
confidence: 99%
“…A previous study found that girls were superior to boys in achievement goal orientations, which indicated that girls possessed higher mastery-approach goals and lower performance-avoidance goals ( Mouratidis et al, 2017 ). Male students are more performance-oriented than females ( Butler, 2014 ; Yu and McLellan, 2019 ). Moreover, girls were more apt at engaging in learning than are boys ( Li et al, 2011 ; Salmela-Aro and Upadaya, 2012 ; Wang and Eccles, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, mastery-approach and performance-approach goals indicate positive effects on the academic adjustment while mastery-avoidance and performance-avoidance goals indicate negative effects ( Baranik et al, 2010 ; Van Yperen et al, 2015 ; Tian et al, 2017 ; Honicke et al, 2020 ). Most studies suggested that girls possess higher mastery-approach goals and lower performance-avoidance goals and boys are more performance-oriented than girls ( Butler, 2014 ; Mouratidis et al, 2017 ; Yu and McLellan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that social development goal structures, defined as a positive social classroom climate focusing on interpersonal growth and improving social competencies (e.g. Makara and Madjar 2015;Ryan and Shim 2006;Yu and McLellan 2019), should be positively related to mastery goals as a personal motivational pattern in the academic domain with a similar orientation towards growth and the enhancement of competencies (Hypothesis 3).…”
Section: Social Developmental Goal Structures Predicting Mastery Goalsmentioning
confidence: 99%